Represión y dictadura: la praxis del sindicalismo combativo a través del caso de los obreros metalúrgicos del sur santafesino - Agustín Prospitti (Nuevo mundo - Mundos Nuevos, 2014)
The aim of this essay is to analyze the repressive actions which began in the middle seventies deeply affected by the military coup d’Etat of the 1976 up to the return of democracy in 1983. We would analyze the objectives and impact on society especially on the working class by looking at a case study of the metallurgical workers of huge steelmaking companies placed in the south of Santa Fe province in Argentina.